2007
DOI: 10.1111/j.1365-3059.2007.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cultivar mixtures on scab control in apple orchards

Abstract: The effects of two mixtures of resistant and susceptible apple cultivars on the development of scab caused by Venturia inequalis were observed in an experimental orchard over four years, initially for two years without fungicides against scab, and subsequently for two years with a moderate fungicide schedule. The row-by-row and within-row mixtures included a susceptible cultivar and a resistant cultivar in equal proportions. Without fungicides, the results showed a significant reduction of disease incidence ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…Our results are consistent with observed effects of diversification strategies on pathogen dynamics. While, random mixtures are reported to provide better disease control than do alternating rows (Mundt 2002, Didelot et al 2007, row mixtures are more practical in application and they can be sufficiently effective in disease suppression on a large scale (Zhu et al 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with observed effects of diversification strategies on pathogen dynamics. While, random mixtures are reported to provide better disease control than do alternating rows (Mundt 2002, Didelot et al 2007, row mixtures are more practical in application and they can be sufficiently effective in disease suppression on a large scale (Zhu et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Recent empirical studies reveal that intraspecific crop diversification might be a possible solution to the vulnerability of monocultured crops to disease (Zhu et al 2000;Mundt 2002;Didelot et al 2007;Finckh 2008). Although numerous theoretical and empirical studies highlight the importance of the host genetic heterogeneity in the pathogen evolution and invasion (Hastings et al 2005;Melbourne et al 2007), little effort has been directed to investigate how spatial patterning of a genetically diverse host affects the ecological and evolutionary dynamics of the pathogen (Alphey et al 2008;Boots and Sasaki 1999;Boots et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mixture effect was higher when the disease was initiated by artificial focal inoculation (Beijing and Gangu) rather than that initiated naturally (Yanting). For instance, in the Gangu field in 2007-2008 growing season, the disease incidence was decreased by 53.3% in mixture of resistant cultivar 9220-42 with the susceptible Shi917 at 1:1 against Relative effectiveness of cultivar mixture (REM) on disease incidence Modelling studies (Mundt and Brophy 1988;Xu and Ridout 2000) and field experiments (Mundt et al 1996;Andrivon et al 2003;Cox et al 2004;Didelot et al 2007) have shown that the rate of disease increase in mixtures can be reduced significantly, compared to those on susceptible pure stands, but the period of time when cultivar mixture can affect epidemic development has still not been determined. In this study, the rates of stripe rust development of most mixtures were significantly less than those of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, even the cultivars showing susceptibility to the race (6) isolate displayed resistance to the mixed inoculum UPNA99, while they should predictably behave as susceptible, because this inoculum contains race (6). We do not have a satisfactory explanation for this behaviour, but it is conceivably influenced by different factors, such as the occurrence of pathogenic diversity among isolates classified as race (6); the presence of other races in the mixed inoculum that could trigger an effective defence response in the host, particularly if race (6) was in a low proportion; the existence of a level of polygenic resistance in these cultivars contributing to disease avoidance, or the fact that mixtures of cultivars effectively reduce the incidence and severity of apple scab (Didelot et al 2007). The appearance and widespread occurrence of race (6) pathotypes, which overcome the resistance conferred by gene Rvi6, has prompted the search for new sources of durable resistance and the necessity to combine different resistance genes in the same genotype (pyramiding).…”
Section: Discussionmentioning
confidence: 99%